Designing Educational Curriculum Management at HSPG Sidoarjo Homeschooling - Oktarini, Diana (PT Ilmu Inovasi Nusantara, 2024)
This study aims to determine the management of the educational curriculum in the HSPG Sidoarjo homeschooling which has implemented the Merdeka Belajar program and the Pancasila student profile. The research approach is qualitative with a descriptive research type. The study subjects were the principal and all stakeholders in the HSPG Sidoarjo Homeschooling. Data collection techniques include observation, interviews, and documentation. Data analysis in this study includes data reduction, data presentation, and conclusion. The research obtained in this study concerns the planning, implementation, and evaluation process of the HSPG Sidoarjo homeschooling curriculum. It is hoped that this research will positively contribute to determining a superior curriculum in the field of competence and good performance for all homeschooling institutions.